Analisis Efektivitas Program Keluarga Harapan Dalam Upaya Meningkatkan Kesejahteraan Masyarakat di Nagari Koto Tangah Batu Ampa Kecamatan Akabiluru - Reni Addera Damanik; Weriantoni Weriantoni; Putri Ayu; Resi Pratiwi (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2023)
The Family Hope Program is a type of conditional social assistance provided by the government to poor families in the form of health, education and social welfare costs. This study aims to determine the effectiveness of PKH in an effort to improve people's welfare in Nagari Koto Tangah Batu Ampa. The subjects of this study were Beneficiary Families (KPM), which consisted of 82 respondents who were in Nagari Koto Tangah Batu Ampa. The method used is a qualitative approach method, and the results of the research are explained using descriptive analysis. Measuring effectiveness based on the Ministry of Home Affairs RD standards through indicators of program understanding, target accuracy, timeliness, goal achievement, and real change. Overall the analysis of the effectiveness of the Family Hope Program in improving people's welfare in Nagari Koto Tangah Batu Ampa is stated to be quite effective, with an average result of calculating all variables of 71.70%. It can be interpreted that the PKH assistance funds provided by the government have been sufficient to help improve the economic welfare of the KPM community, especially in accessing education, health and social welfare services.